Rapid screening and multi-toxin profile confirmation of tetrodotoxins and analogues in human body fluids derived from a puffer fish poisoning incident in New Caledonia. (February 2018) - Rambla-Alegre, Maria; Leonardo, Sandra; Barguil, Yann; Flores, Cintia; Caixach, Josep; Campbell, Katrina; Elliott, Christopher T.; Maillaud, Claude; Boundy, Michael J.; Harwood, D. Tim; Campàs, Mònica; Diogène, Jorge
Abstract: In August 2014, a puffer fish poisoning incidence resulting in one fatality was reported in New Caledonia. Although tetrodotoxin (TTX) intoxication was established from the patients' signs and symptoms, the determination of TTX in the patient's urine, serum or plasma is essential to confirm the clinical diagnosis. To provide a simple cost-effective rapid screening tool for clinical analysis, a maleimide-based enzyme-linked immunosorbent assay (mELISA) adapted for the determination of TTX contents in human body fluids was assessed. The mELISA was applied to the analysis of urine samples from two patients and a response for the presence of TTX and/or structurally similar analogues was detected in all samples. The analysis by LC-MS/MS confirmed the presence of TTX but also TTX analogues (4- epi TTX, 4, 9-anhydroTTX and 5, 6, 11-trideoxyTTX) in the urine. A change in the multi-toxin profile in the urine based on time following consumption was observed. LC-MS/MS analysis of serum and plasma samples also revealed the presence of TTX (32.9 ng/mL) and 5, 6, 11-trideoxyTTX (374.6 ng/mL) in the post-mortem plasma. The results provide for the first time the TTX multi-toxin profile of human samples from a puffer fish intoxication and clearly demonstrate the implication of TTX as the causative agent of the reported intoxication case. Highlights: First report that describes the TTX multi-toxin profile in urine and post-mortem plasma after puffer fish consumption. A user-friendly screening and quantification analysis tool for TTX in urine samples is provided. Excellent correlation of LC-MS/MS and mELISA is obtained in the analysis of urine samples. A change in the TTX multi-toxin profile in the urine based on time following consumption is observed. Analysis of urine and plasma confirmed the presence of TTXs and demonstrates their implication in the intoxication.